Spatial distribution of radiogenic heat in the Iullemmeden basin – Precambrian basement transition zone, NW Nigeria - Aisabokhae, Joseph; Adeoye, Moses (Geology, Geophysics and Environment, 2020)
The area which transcends the Precambrian basement complex onto the Sokoto sector of the Iullemme-den basin in northwestern Nigeria presents a unique prospect for geothermal exploration research in the absence of regional heat production data, despite its tectonic history and depositional characteristics. In this study, geophysical exploration employing radiometric technique was adopted to classify the petrologic units within the fringes of the Iullemmeden basin and the adjoining crystalline basement complex so as to estimate the radiogenic heat potential within the terrain that may support geothermal considerations. Airborne radiometric measurements acquired over the area were digitized and processed to obtain radioelement concentration maps and the K/Th/U ternary map. Results show that the ranges of measured concentrations of 40K, 238U and 232Th are 4.6 to 18.9%, 0.7 to 4.9 ppm and 4.6 to 18.9 ppm respectively. Radiogenic heat estimation derived from radioelement data within eight petrologic units comprising quaternary sediments, schist, carbonates, shale/clay, younger granites, older granites, gneissic rock and migmatite showed that the lowest radiogenic heat production estimates ranging from 0.27–0.66 μW∙m−3 were recorded in the sedimentary terrain within the quaternary sediments while the highest radiogenic heat production values of between 2.04 to 2.34 μW∙m−3 were recorded in the basement com-plex within gneissic rocks. The spatial distribution of radiogenic heat in the area showed an increased heat gradient within the basement complex and a diminishing heat gradient over the Iullemmeded basin.